INHIBITORS OF ANGIOGENESIS IN BRAIN TUMORS – REVIEW - Mindov I.; Petrov B.; Atsev S.; Valkanov S. (Science & Research)

(untitled)
Malignant glial and metastatic tumors are highly vascularized tumors and like all solid tumors, they require angiogenesis for their growth. [1] For glioblastoma (GBM) this microvascularization is very likely and those vessels have abnormal structure, shape and organization.[2] The permeability of those blood vessels is high and very variable in space and time.[3, 4] This abnormal permeability and aberrant morphologic vascularnetworkare associated with abnormal - blood flow, oxygen and nutrients delivery, and also decreased delivery of applied systemic medications.[5] The microenviorment of the tumor has zones of hypoxia, interstitial hypertension and necrosis.[6, 7, 8, 9, 10] According to Hobbs et al., when the tumor’diameter reaches 1-2mm,the integrity of blood brain barrier (BBB) is structurally and functionally impaired. The abnormal permeability and еfflux can be visualized on MRI/CT scan imaging as enchancement of the contrast.